2011
DOI: 10.1186/1742-2094-8-82
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens regulate neuroinflammatory genes via estrogen receptors α and β in the frontal cortex of middle-aged female rats

Abstract: BackgroundEstrogens exert anti-inflammatory and neuroprotective effects in the brain mainly via estrogen receptors α (ERα) and β (ERβ). These receptors are members of the nuclear receptor superfamily of ligand-dependent transcription factors. This study was aimed at the elucidation of the effects of ERα and ERβ agonists on the expression of neuroinflammatory genes in the frontal cortex of aging female rats.MethodsTo identify estrogen-responsive immunity/inflammation genes, we treated middle-aged, ovariectomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 78 publications
(103 reference statements)
2
45
0
Order By: Relevance
“…Concentrations of E2 and isotype-selective ER agonists were calculated to produce a release rate of 2.0µg/d and 20 µg/d, respectively. Treatments with E2 and LE2 at these doses result in a similar increase in uterine weight, while DPN causes no change [43]. Body weights were measured to test efficacy of the treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Concentrations of E2 and isotype-selective ER agonists were calculated to produce a release rate of 2.0µg/d and 20 µg/d, respectively. Treatments with E2 and LE2 at these doses result in a similar increase in uterine weight, while DPN causes no change [43]. Body weights were measured to test efficacy of the treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Another group examining neuro-cortical outcomes in rodents found that ERα agonists regulated S100A8/A9 gene expression, which suggested an estrogenic link [85]. However, the regulation of S100A8/A9 in human skin remains unclear as to the estrogenic mechanism of regulation via the ER subtypes.…”
Section: Human Skin Gene Expressionmentioning
confidence: 99%
“…Recent studies indicate novel roles for estrogens in the regulation of neuroendocrine, autonomic and behavioral responses to stress. In this regard, estrogens have also been shown to modulate related functions such as inflammatory processes, pain, anxiety, depressive-like behaviors and cognitive function (14). In this review, we focus on some of the roles for estrogens and estrogen receptors (ERs) in the control of stress and stress-related behaviors and address a few of the molecular mechanisms that might drive these regulatory processes.…”
Section: Introductionmentioning
confidence: 99%